The Impact of Foreign Direct Investment (FDI) on Economic Growth in Deli Serdang Regency 2015-2024 - Evida Rahimah; Zulaili; Radiah; Supriono; Ilfi Rahmi Putri (Jurnal QOSIM : Jurnal Pendidikan, Sosial & Humaniora, 2026)
This study is entitled "The Effect of Foreign Direct Investment (PMA) on Economic Growth in Deli Serdang Regency". The purpose of this study is to determine and analyze the effect of Foreign Direct Investment (PMA) on Economic Growth in Deli Serdang Regency. The technique used in this study is Ordinary Least Square (OLS) using a simple regression analysis method. The data used in this study is annual data (10 years) published in the Central Statistics Agency of Deli Serdang Regency. The results of the study indicate that the independent variable or Foreign Direct Investment (PMA) has a negative and insignificant effect on economic growth, meaning that PMA is not able to increase economic growth in Deli Serdang Regency.